2022
DOI: 10.3389/fcvm.2022.847554
|View full text |Cite
|
Sign up to set email alerts
|

3D Tissue-Engineered Vascular Drug Screening Platforms: Promise and Considerations

Abstract: Despite the efforts devoted to drug discovery and development, the number of new drug approvals have been decreasing. Specifically, cardiovascular developments have been showing amongst the lowest levels of approvals. In addition, concerns over the adverse effects of drugs to the cardiovascular system have been increasing and resulting in failure at the preclinical level as well as withdrawal of drugs post-marketing. Besides factors such as the increased cost of clinical trials and increases in the requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 288 publications
0
12
0
Order By: Relevance
“…3D cell cultures have the potential to closely emulate the architecture and function of our native tissues. [ 1 ] Material‐free microtissues in the form of cellular spheroids or organoids are considered the most biomimetic 3D culture models with myriad applications including disease modeling, [ 2 ] drug screening, [ 3 ] and modular tissue engineering. [ 4 ] 3D microtissues are typically formed via self‐assembly through cell–cell interactions within a non‐cell‐adhesive environment, such as a hanging drop, nonadhesive microwell, or spinner flask.…”
Section: Introductionmentioning
confidence: 99%
“…3D cell cultures have the potential to closely emulate the architecture and function of our native tissues. [ 1 ] Material‐free microtissues in the form of cellular spheroids or organoids are considered the most biomimetic 3D culture models with myriad applications including disease modeling, [ 2 ] drug screening, [ 3 ] and modular tissue engineering. [ 4 ] 3D microtissues are typically formed via self‐assembly through cell–cell interactions within a non‐cell‐adhesive environment, such as a hanging drop, nonadhesive microwell, or spinner flask.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Still, only a limited number of these used iPSC-derived vascular cells to create a bilayered TEVG. [38,39,42] Nakayama et al successfully produced bilayered aligned nanofibrillar collagen graft, using iPSC-derived vascular cells as a cell source and demonstrated in their experiments that EC-seeded aligned scaffolds significantly reduced inflammatory response, based on monocytes adhesion and thus provided an atheroprotective function, even without application of flow on these constructs . [38] In 2019, the group of Generali et al also demonstrated a PGA-based bilayered vascular graft based on both iPSC-derived endothelial cells and vascular smooth muscle cells under flow.…”
Section: (11 Of 16)mentioning
confidence: 99%
“…Particularly demanding is the development of 3D tissue engineered blood vessels, due to their multi-layered cellular composition (endothelial cells, smooth muscle cells, and pericytes), which varies depending on vessel location, lumen size and function; exposure to flow and shear conditions, and expression of vascular tissue functions, including vasoactivity, permeability and secretory functions [ 91 ]. Several vascular 3D models are in development, as recently reviewed in [ 91 ], ranging from simpler scaffold-free and scaffold-based 3D models [ 92 ], to bioprinting techniques, dynamic culture in bioreactors and microfluidic systems. An additional challenge to these approaches is posed by tumor-associated vessels, which, as discussed above, are abnormal, making even more difficult to model a reliable TME suitable to assess the impact of anti-angiogenic therapies.…”
Section: Moving From 2d To 3d Cultures To Model Tumor Microenvironmentmentioning
confidence: 99%